Binding in working memory and frontal lobe in normal aging: is there any similarity with autism? - Lecouvey, Grégory; Quinette, Peggy; Kalpouzos, Grégoria; Guillery-Girard, Bérengère; Bejanin, Alexandre; Gonneaud, Julie; Abbas, Ahmed; Viader, Fausto; Eustache, Francis; Desgranges, Béatrice (Frontiers in Human Neuroscience, 2015)
Some studies highlight similarities between Autism Spectrum Disorder (ASD) and healthy aging. Indeed, the decline in older individuals’ ability to create a unified representation of the individual features of an event is thought to arise from a disruption of integration within the episodic buffer of working memory as the same way as observed in ASD. In both cases, this deficit may result from an abnormal engagement of a frontohippocampal network. The objective of the present study is to identify both cognitive processes and neural substrates associated to the deficit of integration in healthy aging. We studied the capacity of integration and the cognitive processes that might mediate its decline in 72 healthy participants aged 18-84 years. We confronted the behavioral data to the changes in brain metabolism associated with the age-related decline in a subgroup of 34 healthy participants aged 20-77 years using the resting-state [18F] fluorodeoxyglucose positron emission tomography (18F-FDG PET). Forward stepwise regression analyses showed that the age-related decline in binding was partially explained by a decline in inhibition and processing speed. PET correlation analyses indicated that metabolism of the medial frontal regions, anterior and middle cingulate cortices is implicated in this phenomenon. These data suggest that executive functions and processing speed may play a crucial rule in the capacity to integrate unified representations in memory in aging. Possible implications are discussed in ASD.